The Impact of Foreign Direct Investments (FDIs) on Economic Growth: The Solow Model in the Case of Albania - Lleshaj, Llesh; Malaj, Arben (European Journal of Economics and Business Studies, 2016)
In the developing countries, including Albania, attracting FDIs remains a government priority towards development of investments and the whole economy. Therefore, the main objective of this paper is to analyze the impact of FDIs on economic growth (GDP level) in Albania. The analysis is based on the neoclassical growth model, following the Solow model. The dependent variable in the model is the GDP level and independent variables are: capital (foreign and domestic capital investments) and labor (average salary) for the period 1996-2013 with quarterly data. The results of the econometric analysis indicate that the Solow model is applicable in the Albanian economy, showing a positive correlation which is statistically significant between the explanatory variables and the dependent variable both in the short and long run. The impact of FDIs on GDP is several times smaller than the impact of domestic capital investments. This elasticity can be explained by the lower level of FDI inflows compared to the domestic capital investments and the limitations in evaluating the "endogenous" growth of FDIs. Whereas the analysis of the sector and country of origin concentration of the FDI stock is done using the Herfindal - Hirschman index for the period 2007-2013 and the results determine a significant concentration of FDI stock, based on three sectors and a few countries of origin.